Prevalence Trichomoniasis and Candidiasis For Symptomatic Pregnant and Non Pregnant Women in Iraq - Dhilal Mahdi AL-Muathen; Hayat Ghaith Sachit (College of Pharmacy / Mustansiriyah University, 2018)
The prevalence of Trichomonas vaginalis (TV) and Candida albicans (CA) has been determined in 182 symptomatic married women (70 pregnant and 112 non pregnant) randomly selected from private gynecology clinics in Baghdad city. The relationship between infection and some risk factors was assessed.             Data were collected by questionnaire and vaginal swabs were examined microscopically. Of the 182 women the pregnant 4 infected with TV and19 with CA while non-pregnant 2 infected with TV and 14 with CA.             The age group between (20-29years) represents the highest frequency of infection with the two microorganisms. Abortion number and monthly family income were statistically non significant with high infection rates.